2019
DOI: 10.1016/j.childyouth.2018.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Foster care placement instability: A meta-analytic review

Abstract: Foster care is the preferred type of out-of-home placement for children and youth when they are not able to live with their own parents. However, placement instability, and its effect on children's behavioral well-being, remains a major issue in foster care. Ten multilevel meta-analyses were performed to examine factors that can affect instability of foster care placement. We included 42 studies (published between 1990 and 2017) examining putative factors associated with placement instability, which yielded 29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
3
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(96 citation statements)
references
References 96 publications
4
77
3
3
Order By: Relevance
“…As noted earlier, sex differences were found with respect to placement instability in the previous year, with girls more likely to have experienced three or more placements. This finding deviates from a recent meta‐analysis of 42 papers that indicated that placement instability was unrelated to sex (Konijn et al, ). They reported that placement instability was related to the older age, the young person's behaviour problems, placement in nonkinship care, and history of maltreatment (Konijn et al, ).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…As noted earlier, sex differences were found with respect to placement instability in the previous year, with girls more likely to have experienced three or more placements. This finding deviates from a recent meta‐analysis of 42 papers that indicated that placement instability was unrelated to sex (Konijn et al, ). They reported that placement instability was related to the older age, the young person's behaviour problems, placement in nonkinship care, and history of maltreatment (Konijn et al, ).…”
Section: Discussioncontrasting
confidence: 99%
“…It remains unclear as to whether improving mental health and wellbeing of these young people improves relationships with carers and thus promotes placement security. Case workers can help minimize placement instability by ensuring appropriate matching of the young person to the carer, screening the young people for behavioural issues and stress, upskilling foster carers on how to manage such issues, providing ongoing monitoring of placement outcomes, and implementing interventions to minimize problems in a placement (Konijn et al, ). If there is early termination of a placement, the case worker should provide adequate support for the young person and carer to manage that transition (Zeijlmans, López, Grietens, & Knorth, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of this study was to examine change in foster children's mental health over time and how this change depends on characteristics related to the foster child, the child's care experiences, foster family, and foster placement. Foster children's mental health is an important predictor of foster placement success (Konijn et al 2019). We found that levels of mental health were stable over time, meaning that, on average, there were no increasing or decreasing trends in prosocial, internalizing, and externalizing behaviors during the one year study period.…”
Section: Discussionmentioning
confidence: 68%
“…To optimize foster children's development, we need to know more about the characteristics that predict to foster children's positive developmental outcomes. Our focus is on foster children's mental health, because it is an important indicator of the quality of foster children's developmental trajectories and after care outcomes (Dixon 2008;Konijn et al 2019;Oosterman et al 2007).…”
Section: Introductionmentioning
confidence: 99%